(untitled) - Cengel, Yunus A. (Boston, 2002)
A self instructive text for thermodynamics. This is the second edition of the title which can be supplemented by a solutions manual, OHT's and an IBM disk
Keywords: Thermodynamics,Nhiệt động lực học